Effects of fiber orientations and fiber types of composite laminated plates - C.W. Pein; Hakim S., Sultan Aljibori; Mahlia, T.M.I.; Haidar Alqrmili; Togun, H.; Irfan Anjum (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.